2014
DOI: 10.3390/molecules191015735
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Scale Computational Study on the Mechanism of Streptococcus pneumoniae Nicotinamidase (SpNic)

Abstract: Nicotinamidase (Nic) is a key zinc-dependent enzyme in NAD metabolism that catalyzes the hydrolysis of nicotinamide to give nicotinic acid. A multi-scale computational approach has been used to investigate the catalytic mechanism, substrate binding and roles of active site residues of Nic from Streptococcus pneumoniae (SpNic). In particular, density functional theory (DFT), molecular dynamics (MD) and ONIOM quantum mechanics/molecular mechanics (QM/MM) methods have been employed. The overall mechanism occurs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Inter lies 2.4 kcal mol −1 higher in energy than TS1 and is able to reversibly rearrange back to the reactive complex essentially without a barrier. That TS’s relative energy is lower than Inter’s is a common artifact of the use of zero-point vibrational energy (ZPVE) correction and/or empirical corrections on flat potential energy surface313233. Interestingly, in our specific system, the stabilization effect on TS1 from ZPVE correction happens to be more significant than that of Inter.…”
Section: Resultsmentioning
confidence: 79%
“…Inter lies 2.4 kcal mol −1 higher in energy than TS1 and is able to reversibly rearrange back to the reactive complex essentially without a barrier. That TS’s relative energy is lower than Inter’s is a common artifact of the use of zero-point vibrational energy (ZPVE) correction and/or empirical corrections on flat potential energy surface313233. Interestingly, in our specific system, the stabilization effect on TS1 from ZPVE correction happens to be more significant than that of Inter.…”
Section: Resultsmentioning
confidence: 79%
“…It can be noted that the reaction likely occurred without an energy barrier, since the IM1 was slightly higher than that of the TS1. This is a common result of using single-point calculations or empirical corrections on potential energy surfaces (PESs), which can be avoided at a higher level of theory calculation, without the inclusion of the environment’s electrostatic charge [36].…”
Section: Resultsmentioning
confidence: 99%
“…The alignment also revealed that PolyNic contained all the conserved catalytic triad residues of the cysteine-hydrolases family ( Figure 5 , filled circles): a catalytic cysteine at position 150 (C150, PolyNic numbering), an aspartate at position 25 (D25) and a lysine at position 111 (K111) (French et al, 2010b; Sanchez-Carron et al, 2013; Ion et al, 2014; Sheng and Liu, 2014). Furthermore, PolyNic showed the characteristic cis -peptide bond ( Figure 5 , positions L145 and A146, filled squares), which is invariably preceded by a conserved glycine (G144), and the conserved specific metal ion binding, which includes one aspartate (D67) and two histidines (H69 and H86) ( Figure 5 , filled triangles).…”
Section: Resultsmentioning
confidence: 99%